Campaigning for the Japanese Lower House: From Mobilising to Chasing Voters? - Patrick Köllner (German Institute of Global and Area Studies (GIGA), 2007)
Electioneering for the Japanese Lower House has undergone significant changes in recent years. Not only institutional but also other environmental changes are pushing political actors in Japan to complement the hitherto dominant vote-mobilisation approach by vote-chasing strategies. Such strategies target in particular unaffiliated voters and emphasise party leaders. Yet, the notion of an 'Americanisation' of campaigning in Japan seems pre-mature at best. Notably, electioneering for the Lower House has become more party-oriented in the course of introducing new voter chasing strategies. It remains to be seen though whether specific campaign instruments and tactics used in recent general elections, such as the manifesto approach, can generate value-added in the longer term. – – Der Wahlkampf für das japanische Unterhaus hat sich in den vergangenen Jahren in bedeutsamer Weise verändert. Nicht allein institutionelle, sondern auch andere Umweltveränderungen veranlassen parteipolitische Akteure dazu, den bisher dominanten Stimmenmobilisierungsansatz durch Strategien zur Jagd auf Wählerstimmen (vote chasing) zu ergänzen. Solche Strategien zielen insbesondere auf parteiungebundene Wähler ab und rücken Parteiführer in den Mittelpunkt. Indes kann von einer 'Amerikanisierung' von Wahlkämpfen in Japan kaum die Rede sein. So sind Wahlkämpfe im Zuge der Einführung neuer Strategien zur Jagd auf Wählerstimmen tendenziell parteizentrierter geworden. Offen muss zunächst bleiben, ob spezifische Wahlkampfinstrumente und -taktiken, die bei allgemeinen Wahlen der jüngeren Zeit Einsatz gefunden haben - wie etwa der Manifest-Ansatz - nachhaltig Wirkung entfalten werden.
Keywords: 300; election campaigning; mixed-member electoral system; voter targeting; Americanisation thesis; Japan